Prominent bradycardia in a COVID-19 patient receiving Remdesivir: a case report - Sidhi Laksono Purwowiyoto; Grace Trifena Hosea (Universitas Muhammadiyah Surabaya, 2022)
Remdesivir is a commonly used antiviral drug to treat COVID-19. Remdesivir has some side effects; however, whether it has any effect on cardiac is rarely reported. A 44-year-old woman with symptomatic confirmed COVID-19 was treated with intravenous remdesivir 200 mg on day one and followed with 100 mg remdesivir until day five. Three days after the treatment, she had significant bradycardia shown on the electrocardiography; however, the patient had no complaint or symptom regarding the bradycardia. Based on the discussion with the cardiology team, it was decided to cease remdesivir and replace it with oseltamivir, and the ECG showed some improvement. Remdesivir is a drug that should be used safely and cannot be taken at home, as there may be side effects left unaware.